Fear Conditioning is Disrupted by Damage to the Postsubiculum - Robinson, Siobhan (2011)
The hippocampus plays a central role in spatial and contextual learning and memory, however relatively little is known about the specific contributions of parahippocampal structures that interface with the hippocampus. The postsubiculum (PoSub) is reciprocally connected with a number of hippocampal, parahippocampal and subcortical structures that are involved in spatial learning and memory. In addition, behavioral data suggest that PoSub is needed for optimal performance during tests of spatial memory. Together, these data suggest that PoSub plays a prominent role in spatial navigation. Currently it is unknown whether the PoSub is needed for other forms of learning and memory that also require the formation of associations among multiple environmental stimuli. To address this gap in the literature we investigated the role of PoSub in Pavlovian fear conditioning. In Experiment 1 male rats received either lesions of PoSub or Sham surgery prior to training in a classical fear conditioning procedure. On the training day a tone was paired with foot shock three times. Conditioned fear to the training context was evaluated 24 hr later by placing rats back into the conditioning chamber without presenting any tones or shocks. Auditory fear was assessed on the third day by presenting the auditory stimulus in a novel environment (no shock). PoSub-lesioned rats exhibited impaired acquisition of the conditioned fear response as well as impaired expression of contextual and auditory fear conditioning. In Experiment 2, PoSub lesions were made 1 day after training to specifically assess the role of PoSub in fear memory. No deficits in the expression of contextual fear were observed, but freezing to the tone was significantly reduced in PoSub-lesioned rats compared to shams. Together, these results indicate that PoSub is necessary for normal acquisition of conditioned fear, and that PoSub contributes to the expression of auditory but not contextual fear memory.